2019
DOI: 10.1093/biolre/ioz129
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial luminal epithelial cells sense embryo elongation in the roe deer independent of interferon-tau†

Abstract: Numerous intrauterine changes take place across species during embryo development. Following fertilization in July/August, the European roe deer (Capreolus capreolus) embryo undergoes diapause until embryonic elongation in December/January. Embryonic elongation prior to implantation is a common feature among ungulates. Unlike many other ruminants, the roe deer embryo does not secrete interferon-tau (IFNτ). This provides the unique opportunity to unravel IFNτ-independent signaling pathways associated with mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…The BrdU incorporation in trophoblast cells as measure for cell proliferation increased from 5 % in October/November to 10 % in November/December [29], and there was a 22.5-fold higher protein incorporation at elongation versus diapause [23,24]. By numerous field sample collections, our group substantiated earlier reports [1-3, 25, 28, 29] of a continuous increase in embryonic size with time (Figure 1) (Unpublished data; Rüegg et al 2019 Trophectoderm and Embryoblast of the European Roe Deer (Capreolus capreolus) both proliferate at slow pace during Embryonic Diapause) [4][5][6]. In.…”
Section: Embryosupporting
confidence: 88%
See 2 more Smart Citations
“…The BrdU incorporation in trophoblast cells as measure for cell proliferation increased from 5 % in October/November to 10 % in November/December [29], and there was a 22.5-fold higher protein incorporation at elongation versus diapause [23,24]. By numerous field sample collections, our group substantiated earlier reports [1-3, 25, 28, 29] of a continuous increase in embryonic size with time (Figure 1) (Unpublished data; Rüegg et al 2019 Trophectoderm and Embryoblast of the European Roe Deer (Capreolus capreolus) both proliferate at slow pace during Embryonic Diapause) [4][5][6]. In.…”
Section: Embryosupporting
confidence: 88%
“…With developmental progression, there was a decrease in electron-dense droplets and elongation was characterized by the presence of cell organelles, suggesting a higher proliferation rate and increased metabolic demands [28]. While the embryos were not found to secrete interferon tau (IFNT) prior to implantation [6,22], the embryos secreted roe deer-specific pregnancy associated glycoproteins (PAGs) upon implantation [26]. An interspecies embryo transfer experiment with mice, a species with facultative diapause, and sheep, a species without diapause, showed that the mouse uterine environment induced diapause in sheep embryos [15].…”
Section: Embryomentioning
confidence: 99%
See 1 more Smart Citation
“…Maternal factors involved in governing the cell cycle may be elucidated. They may further our understanding of molecular factors in the uterine microenvironment that play a role in stem cell pluripotency (Drews et al 2019;van der Weijden et al 2019avan der Weijden et al , 2019bvan der Weijden et al , 2019c. The findings may be translatable to other species, including bovine and human.…”
Section: Future Directionsmentioning
confidence: 83%
“…Thus, the lack of change of the progestogens in roe deer indicates that they are likely not involved reactivation of embryo development. We have previously shown the loss of uterine PR with prolonged P4 exposure [25]. As the progestogens are present in significant amounts, they might play a role in priming the uterus like in mice.…”
Section: Discussionmentioning
confidence: 98%